2019
DOI: 10.1128/jvi.02098-18
|View full text |Cite
|
Sign up to set email alerts
|

Equine Herpesvirus 1 Bridles T Lymphocytes To Reach Its Target Organs

Abstract: Equine herpesvirus 1 (EHV1) replicates in the respiratory epithelium and disseminates through the body via a cell-associated viremia in leukocytes, despite the presence of neutralizing antibodies. “Hijacked” leukocytes, previously identified as monocytic cells and T lymphocytes, transmit EHV1 to endothelial cells of the endometrium or central nervous system, causing reproductive (abortigenic variants) or neurological (neurological variants) disorders. In the present study, we questioned the potential route of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 95 publications
1
26
0
1
Order By: Relevance
“…In addition, a study showed that N 752 strains (isolated from abortion) could infect equally monocytic CD172a+ cells and T lymphocytes, whereas D 752 strains (isolated from neurological cases) could infect CD172a+ cells in a larger proportion than T lymphocytes. In accordance with other studies, the authors suggested that N 752 had adapted its immune evasion strategy after co-evolving from D 752 strains with the host immune system [ 52 , 54 , 55 ]. Concerning the genotype/pathotype association suggested by Nugent et al (2006), it was followed by a statistical report by Perkins et al performed on 176 EHV-1 isolates, showing a strong but not strict association between G 2254 /D 752 strains and neurological disease, and A 2254 strains and abortion disease.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, a study showed that N 752 strains (isolated from abortion) could infect equally monocytic CD172a+ cells and T lymphocytes, whereas D 752 strains (isolated from neurological cases) could infect CD172a+ cells in a larger proportion than T lymphocytes. In accordance with other studies, the authors suggested that N 752 had adapted its immune evasion strategy after co-evolving from D 752 strains with the host immune system [ 52 , 54 , 55 ]. Concerning the genotype/pathotype association suggested by Nugent et al (2006), it was followed by a statistical report by Perkins et al performed on 176 EHV-1 isolates, showing a strong but not strict association between G 2254 /D 752 strains and neurological disease, and A 2254 strains and abortion disease.…”
Section: Discussionsupporting
confidence: 86%
“…The viral and host factors responsible for cell-to-cell spread have not yet been fully identified for EHV-1. It was postulated that EC infection is established upon close contact of infected PBMC with EC upon which cell-to-cell virus transfer can take place [ 28 , 29 ]. Factors favoring adhesion of the two cell types and establishing cell-to-cell contact are essential for viral spread [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, EHV-1 infects mononuclear cells, enters the blood circulation and is thereby disseminated widely to secondary infection sites, such as the central nervous system (CNS) or the uterus ( 1 – 3 ). The main cell type infected during cell-associated viremia are monocytes and T-lymphocytes (T-cells), followed by B-lymphocytes (B-cells) ( 4 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…For VZV, which, like EHV-1, belongs to the subfamily of Varicellovirinae, it is thought that VZV is transported to the sensory ganglia during viremia and in VZV-infected T-cells, as well as by axonal transportation ( 24 , 25 ). EHV-1 tropism for T-cells is also well described and it is proposed to be important for viral dissemination throughout the host and for bypassing viral clearance by the immune system ( 7 , 22 , 26 ). Interestingly, while EHV-1 gene transcription and protein expression is active during viral replication in epithelial cells, during viremia, the virus seems to be carried in a non-replicative state, until secondary locations, such as CNS or uterine endothelium, are reached and virus transfer occurs ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation